Tendencies leading the route: Which light vehicles are conquering the Ecuadorian market? - Tobar Franco, Jorge Washington (2025)
Objective: The present study aimed to analyze the evolution of the Ecuadorian automotive park between 2019 and 2023, considering the impact of economic, political, and technological factors on vehicle composition, emissions, and the need for balanced policies in Latin America. Materials and methods: An exploratory methodology based on secondary sources was employed, conducting a systematic review of official data on sales, origin, brand share, and fuel consumption in the light vehicle market in Ecuador. Results: The results obtained evidence a growing preference for sport utility vehicles, in contrast to a decline in demand for cars and trucks. Likewise, stands out the ascent of Asian brands, particularly Chinese ones, which have displaced traditional manufacturers such as Chevrolet. This tendency to been influenced by various factors, between the elimination of fuel subsidies and the increase in VAT, which have changed consumer purchasing decisions. Conclusions: It is concluded that the Ecuadorian automotive market is found in a process of transition toward more efficient and affordable options, with Asian brands playing a key role. In this context, it is recommended to continue with policies that foment sustainable mobility and the adoption of clean technologies, with in order to reduce the environmental impact and ensure balanced development of the sector.